Dihydropyrazole and dihydropyrrole structures based design of Kif15 inhibitors as novel therapeutic agents for cancer. (June 2017) - Sebastian, Jomon
Graphical abstract: Highlights: Generation of pharmacophore hypothesis from dihydropyrazoles and dihydropyrroles. Atom-based QSAR modeling using pharmacophore hypothesis and activity of ligands. Screening of ZINC database for prospective drugs. Ranking of drugs by docking with human Kif15 and calculating binding energy. 4 drugs were predicted for activity using QSAR model and for pharmacokinetics. Abstract: Mitotic Kinesin motors, Eg5 and Kif15, have recently emerged as good targets for cancer as they play an inevitable role during mitosis. But, most of the Eg5 inhibitors were found ineffective when the cancer cells develop resistance to them by escalating the expression of Kif15 as alternative to Eg5. Therefore, the drugs that target Kif15 became necessary to be used either as a single or in combination with Eg5 inhibitors. The present study used 39 dihydropyrazole and 13 dihydropyrrole derivatives that were having in vitro inhibitory potential against kinesin motors to develop a common pharmacophore hypothesis AHRR and atom-based QSAR model. The model was used for virtual screening of ZINC database and the resultant hits were docked against Kif15. The four drug candidates with high docking score were examined for their activity and pharmacokinetic behaviour. Based on the results these drugs could be considered as lead candidates in further drug development for cancer.